The Aesthetic imperative : relevance and responsibility in arts education - Ross, Malcolm, 1932- (Curriculum issues in arts education ;, 1981)
The Aesthetic Imperative: Relevance and Responsibility in Arts Education is a collection of papers that covers various concerns in assessment in the context of arts education.